Applied Environmental Biotechnology: Present Scenario and Future Trends - Kaushik, Garima (Springer, 2015)
Applied Environmental Biotechnology: Present Scenario and Future Trends is designed to serve as a reference book for students and researchers working in the area of applied environmental science. It presents various applications of environmental studies that involve the use of living organisms, bioprocesses engineering technology, and other fields in solving environmental problems like waste and waste waters. It includes not only the pure biological sciences such as genetics, microbiology, biochemistry and chemistry but also from outside the sphere of biology such as chemical engineering, bioprocess engineering, information technology, and biophysics.